Long-Term Outcome in the North East Melbourne Stroke Incidence Study: Predictors of Quality of Life at 5 Years After Stroke - Paul, Seana L.; Sturm, Jonathan W.; Dewey, Helen M.; Donnan, Geoffrey A.; Macdonell, Richard A.L.; Thrift, Amanda G. (Stroke (1970), 2005)
Background and Purpose— Although much is known about the long-term outcome of stroke patients in terms of mortality and disability, there has been little research on the patient-centered outcome of health-related quality of life (HRQoL). There are limited natural history data on HRQoL beyond 2 years after stroke and no data on those factors present at stroke onset that predict HRQoL beyond 2 years after stroke. For these reasons, we aimed to examine these aspects of HRQoL in an unselected population of stroke patients. Methods— All cases of first-ever stroke from a prospective community-based stroke incidence study (excluding subarachnoid hemorrhage) were assessed 5 years after stroke. HRQoL was measured with the assessment of quality of life instrument. ANOVA was used to determine baseline predictors of HRQoL. Results— In total, 978 cases were recruited, 45% were male, and the mean age (±SD) was 75.5±13.8 years. Five years after stroke, 441 (45.1%) were alive and 356 were assessed (80.7%). Those assessed were more often born in Australia and older in age (both P <0.05). Seventy-one survivors (20%) had a very low HRQoL (score ≤0.1). The independent baseline predictors of low HRQoL at 5 years after stroke were increasing age, lower socioeconomic status, and markers of stroke severity. Conclusion— At 5 years after stroke, we found that a substantial proportion of survivors were suffering from poor HRQoL. As our population ages, the number of strokes and, thus, stroke survivors with poor HRQoL is likely to increase. Therefore, strategies to improve HRQoL should be vigorously pursued.